2010
DOI: 10.1080/07347330903438891
|View full text |Cite
|
Sign up to set email alerts
|

A Naturalistic Evaluation of Psychosocial Interventions for Cancer Patients in a Community Setting

Abstract: We used a naturalistic methodology to examine associations between change in cancer patients' emotional functioning and their use of interventions in a community organization. One-hundred ninety-two patients completed measures at baseline and 6 months later. During this time, they utilized the organization's various interventions as they wished. Attendance at educational events was associated with decreased well-being. Use of art therapy groups was not associated with decreases in negative emotion but was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…A number of studies intervened with groups or organizations. However, they did not identify groups or organization as an intervention target nor did they measure any group or organization-level phenomena (18,19,24,29,30,32,40,49,50); they merely measured patient outcomes, sometimes aggregated to the group or organization level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies intervened with groups or organizations. However, they did not identify groups or organization as an intervention target nor did they measure any group or organization-level phenomena (18,19,24,29,30,32,40,49,50); they merely measured patient outcomes, sometimes aggregated to the group or organization level.…”
Section: Discussionmentioning
confidence: 99%
“…Validity also may be approached somewhat differently in multilevel intervention studies; external validity may be emphasized over internal validity. See Shapiro et al (40) for an example where the focus was on external validity in a study of intervention services as routinely delivered within a community.…”
Section: Challenges and Opportunities Associated With Multilevel Measmentioning
confidence: 99%
See 1 more Smart Citation
“…Hund et al (2015) reported that most people with poorer education were females, and those with metastatic tumors have lower levels of adjustment (Hund et al, 2016). Brunault et al investigated and confirmed the negative effects of major depression and young age on adjustment (Brunault et al, 2015), and Jeremy et al also demonstrated the effect of reproach and surrender on poor adjustment (Shapiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Drageset et al (2015) considered intimate family relationships, positive thinking, physical activity, self-care, nature, hobbies, and jobs (Drageset et al, 2016). Moreover, Jeremy et al (2015) considered acceptance of the disease and humor (Shapiro et al, 2010) and Gonzales et al (2015) considered emotional support, religious/spiritual strategies, benefit, belief in destiny, optimism, denial, distraction, and a fighting information-seeking spirit as factors affecting a patient's adjustment to cancer (Gonzales et al, 2015;Gonzalez et al, 2016). Hund et al (2015) reported that most people with poorer education were females, and those with metastatic tumors have lower levels of adjustment (Hund et al, 2016).…”
Section: Introductionmentioning
confidence: 99%